Production of Xylose from Meranti Wood Sawdust by Dilute Acid Hydrolysis - M. Rafiqul, Islam; Mimi Sakinah, A. M.; M. R., Karim (Springer US, 2014)
Xylitol production by bioconversion of xylose can be economically interesting if the raw material can be recovered from a cheap lignocellulosic biomass (LCB). Meranti wood sawdust (MWS) is a renewable and low-cost LCB that can be used as a promising and economic source of xylose, a starting raw material for the manufacture of several specialty chemicals, especially xylitol. This study aimed to optimize the hydrolysis process of MWS and to determine the influence of temperature, H2SO4 concentration, and residence time on xylose release and on by-product formation (glucose, arabinose, acetic acid, furfural,hydroxymethylfurfural (HMF), and lignin degradation products (LDPs)). Batch hydrolysis was conducted under various operating conditions, and response surface methodology was adopted to achieve the highest xylose yield. Xylose production was highly affected by temperature, acid concentration, and residence time. The optimum temperature, acid concentration,and time were determined to be 124 °C, 3.26 %, and 80 min, respectively. Under these optimum conditions, xylose yield and selectivity were attained at 90.6 % and 4.05 g/g,respectively